The brain metabolic activity after resuscitation with liposome-encapsulated hemoglobin in a rat model of hypovolemic shock - Rao, Geeta (J Cereb Blood Flow Metab, 2015)
We examined the effect of resuscitation with liposome-encapsulated hemoglobin (LEH) on cerebral bioenergetics in a rat model of 45% hypovolemia. The rats were resuscitated with isovolemic LEH or saline after 15 minutes of shock and followed up to 6 hours. Untreated hypovolemic rats received no fluid. The cerebral uptake of F-18-fluorodeoxyglucose (FDG) was measured by PET, and at 6 hours, the brain was collected for various assays. Hypovolemia decreased cellular adenosine triphosphate (ATP), phosphocreatine, nicotinamide adenine dinucleotide (NAD)/NADH ratio, citrate synthase activity, glucose-6-phosphate, and nerve growth factor (NGF), even when FDG uptake remained unchanged. The FDG uptake was reduced by saline, but not by LEH infusion. The reduced FDG uptake in saline group was associated with a decrease in hexokinase I expression. The LEH infusion effectively restored ATP content, NAD/NADH ratio, and NGF expression, and reduced the hypovolemia-induced accumulation of pyruvate and ubiquitinated proteins; in comparison, saline was significantly less effective. The LEH infusion was associated with low pH and high anion gap, indicating anionic gap acidosis. The results suggest that hypovolemic shock perturbs glucose metabolism at the level of pyruvate utilization, resulting in deranged cerebral energy stores. The correction of volume and oxygen deficits by LEH recovers the cerebral metabolism and creates a prosurvival phenotype.